An approach to modelling the Impact of international migration on the economy of receiving country - Chernobay, L.; Adamyk, V.; Malibroda, S. (Lviv Politechnic Publishing House, 2019)
Being an objective element of the global economic system, international migration produces a significant impact on the performance of individual countries nowadays. The economic impact of international migration is driven by various factors, primarily the type of international migration (labour migration, refugee migration, family migration, or student migration) and the legislation of a receiving country which determines the ability of international migrants to interact with the host country’s economy and to produce the respective impact. The hypothesis of this study builds on the premise that legislation of the receiving country determines the “capabilities of migrants”, that is a set of actions that can be performed by an international migrant on the territory of receiving country, the consequences of which will produce an impact on the economy of receiving country. We identified the following capabilities: the ability to enter and stay in the country; the ability to be employed; the ability to obtain social protection, education and citizenship; the ability to own and dispose of property. Capabilities are not firmly attached to particular types of international migration. For example, the capability to be employed is associated with such types of migrants as labour migrants, refugees, family and other migrants, depending on the country. The influence of international migrants on the economy of receiving country is determined not by the type of migration, but by the combination of actual capabilities that correspond to certain types of migration. We found five combinations of migrants’ capabilities that determine four types of economic relationships between the migrants and the receiving country’s economy. Each type of economic interaction produces a different effect on the economy of receiving country and can be changed by means of expanding or constraining certain capabilities of migrants, which requires that respective amendments be introduced in the legislation of the receiving country. The scientific appropriateness of our approach to modelling the impact of international migration on the economy of receiving country is based on the analysis of the global legal framework for purposes of identifying the rights that ensure the respective capabilities of migrants, as well as on the application of SNA-2008 principles to modelling the impact of international migration on the economy of receiving country. In this study, we used the method of analysis to single out the rights that ensure the migrant’s capabilities; the method of generalization to reveal attributes, based on which separate rights could be matched with respective capabilities; the method of explanation to describe the notions of “migrant’s capabilities” and “type of economic interaction”; the method of classification to separate specific types of economic interaction; and the method of modelling to describe the relationship between the legislation of the receiving country, the migrants’ capabilities, the types of international migrants, and the impact of such migrants on the economy of receiving country.
Keywords: Impact on the economy; international migration; legislation; migrant’s capabilities; modelling; 339.331.5